2000
DOI: 10.1128/iai.68.1.239-246.2000
|View full text |Cite
|
Sign up to set email alerts
|

Murine Immune Response toNeisseria meningitidisGroup C Capsular Polysaccharide: Analysis of Monoclonal Antibodies Generated in Response to a Thymus-Independent Antigen and a Thymus-Dependent Toxoid Conjugate Vaccine

Abstract: Antibody (Ab) responses to polysaccharides (PSs) such as Neisseria meningitidis group C PS (MCPS) are characterized as being thymus independent (TI) and are restricted with regard to clonotype and isotype expression. PS conjugated to proteins, e.g., MCPS coupled to tetanus toxoid (MCPS-TT), elicits a thymusdependent (TD) response. In order to understand the influence of the form of a vaccine (TI versus TD) on the Ab repertoire, we generated monoclonal antibody (MAb) panels from mice immunized and boosted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…A PROTECTIVE MIMOTOPE OF TYPE 8 PNEUMOCOCCUS 331 the present study, the IgG subclass response resembled that observed for some PS-protein conjugates (18,31,42). Similar to the response to a GXM mimotope (16) and polysaccharide on the surface of whole pneumococci (51), the PUB1-TTinduced type 8 PS response was also characterized by the appearance of IgG early in the response and a lack of significant boosting.…”
Section: Vol 73 2005supporting
confidence: 57%
“…A PROTECTIVE MIMOTOPE OF TYPE 8 PNEUMOCOCCUS 331 the present study, the IgG subclass response resembled that observed for some PS-protein conjugates (18,31,42). Similar to the response to a GXM mimotope (16) and polysaccharide on the surface of whole pneumococci (51), the PUB1-TTinduced type 8 PS response was also characterized by the appearance of IgG early in the response and a lack of significant boosting.…”
Section: Vol 73 2005supporting
confidence: 57%
“…1. Positive controls in the assay include two murine monoclonal antibodies (MAbs), MAbs 706 and 735, with known preferential binding to OAc-negative or OAc-positive polysaccharide, respectively (14). (Antibodies were kindly provided by K. Stein, U.S. Food and Drug Administration, Bethesda, Md.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the response to PPS when conjugated to a protein carrier is dominated by IgG1 in mice and humans (45,50,63,80), and this is considered representative of a T-cell-dependent (TD) response. Although the T-cell response to PPS-based conjugate vaccines has been shown to have TD features, the response can also have characteristics of a TI or an "incomplete" TD response (3,30,38,49,76). The antibody response of Wt mice to PPS3 in our study was consistent with a TD response, with IgG1 as the predominant IgG subclass.…”
Section: Discussionmentioning
confidence: 99%